Effects Of Stress Relaxation On The Pullout Strength Of Pedicle Screws - Razali, Rohana (2016)
Vertebral fixation with pedicle screw is now a mainstay of the spinal instrumentation system. Pedicle screw fixation has been used extensively for spinal stabilization. Screw breakage and loosening are always interrelated with the pedicle screw failure. Failure of the pedicle fixation technique is usually monitored simultaneously with failure that occurred in the bone-screw interface. The aim of this research is to understand essential mechanisms behind the failure of the bone-pedicle screw interface through the stress relaxation manner. The stress relaxation induces damage as loading rate and correspondence time influences the mechanical performance of the bone-screw interface. The effects of viscoelastic properties on the pedicle screw and polyurethane (PU) foam were investigated. The PU foam blocks resembles human cadaveric vertebrae. The specimens of PU blocks were installed with a titanium pedicle screw, and were pull out with the two models: standard pullout and stress relaxation pullout, the latter is a custom pullout protocol that allowed stress relaxation steps during the test. PU blocks of solid rigid closed-cell, and PU blocks with glass fiber reinforced-epoxy (GFRE) sheet were used throughout this study. PU foams of two different density were used to model low and medium-density cancellous bone. Various types (high vs. low) of screw diameter and loading rates were utilized for this study in order to investigate its effects on the stress relaxation. All independent variables were used to establish a mathematical equation for pullout strength and stiffness respectively. The result showed that the stress relaxation had contributed magnitute to the strength and stiffness on the specimen-screw interface. The bone density and GFRE layers significantly (p<0.0001) affect the strength of the fixation. PU showed a characteristic of a solid viscoelastic material as the stress reduced over time.